2018
DOI: 10.1017/s1368980018003245
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of food insecurity among Lebanese households with children aged 4–18 years: findings from a national cross-sectional study

Abstract: ObjectiveFood insecurity (FI) is a major public health problem in Lebanon, a small middle-income country with the highest refugee per capita concentration worldwide and prolonged political and economic challenges. The present study aimed to measure the prevalence and sociodemographic correlates of household FI and to explore the association of household FI with anthropometric measures of children and their mothers.DesignCross-sectional survey (2014–2015).SettingLebanon.ParticipantsNationally representative sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 38 publications
4
42
2
Order By: Relevance
“…Information related to FI was collected using the Household Food Insecurity Access Scale (HFIAS). This tool was developed by USAID's Food and Nutrition Technical Assistance (FANTA) group in early 2000 [33] and it has been validated in Pakistan and other LMICs [20,34]. HFIAS has 9 core questions regarding food intake occurring over the last four weeks (30 days).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information related to FI was collected using the Household Food Insecurity Access Scale (HFIAS). This tool was developed by USAID's Food and Nutrition Technical Assistance (FANTA) group in early 2000 [33] and it has been validated in Pakistan and other LMICs [20,34]. HFIAS has 9 core questions regarding food intake occurring over the last four weeks (30 days).…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents make 24% of Pakistan's population but there are no data on FI estimates of adolescents and its socio-demographic factors [15]. Literature reports that 16-17% adolescents are food insecure in US and Canada [16,17] whereas in developing countries like Ethiopia, Lebanon, and Venezuela 50% of the adolescents are found food insecure [18][19][20]. Belchew et al found the place of residence, lower socio-economic status, dependency ratio, household FI and gender as social determinants of FI among Ethiopian adolescents [18].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no study has been conducted to evaluate the association between HFI and depression among the Iranian pregnant women. Iran is located in the Middle East and North Africa (MENA) region, with a severe food insecurity prevalence of 11%, this country has been recognized as one of the most food-insecure regions in the world (6). Over the last 3 decades, Iran has made a remarkable improvement in reducing food insecurity, so that it has the greatest reduction rate in global hunger index ranking in the Middle East (20).…”
mentioning
confidence: 99%
“…Middle Eastern populations have a high disease burden, which suggests a reduction in routine health service utilization results in increased mortality, a trend expected to hold true for COVID-19 [ 11 , 12 ]. Food insecurity poses a significant public health concern in countries with high refugee per capita concentration, such as Lebanon and Jordan [ 18 - 20 ]. Refugee populations are particularly vulnerable to COVID-19 as they are often concentrated in densely populated camps with poor hygiene measures and fragmented access to health care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%